2017
DOI: 10.7717/peerj.3836
|View full text |Cite
|
Sign up to set email alerts
|

CA1 pyramidal cells have diverse biophysical properties, affected by development, experience, and aging

Abstract: Neuron types (e.g., pyramidal cells) within one area of the brain are often considered homogeneous, despite variability in their biophysical properties. Here we review literature demonstrating variability in the electrical activity of CA1 hippocampal pyramidal cells (PCs), including responses to somatic current injection, synaptic stimulation, and spontaneous network-related activity. In addition, we describe how responses of CA1 PCs vary with development, experience, and aging, and some of the underlying ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 269 publications
(588 reference statements)
2
24
0
Order By: Relevance
“…Hippocampal CA1 pyramidal neurons filled with Alexa Fluor 488 dye (Thermo Fisher Scientific, Rockford, IL, USA) via patch electrode have a distinctive dendritic morphology (Figure a,b). Voltage response to current steps (I‐V curve) with duration of 600 ms ranging from −100 to +200 pA with 20 pA increments, exhibited the characteristic pattern of action potential firing of hippocampal CA1 neurons, with peak depolarization ~50 mV (Martina, Schultz, Ehmke, Monyer, & Jonas, ; McKiernan & Marrone, ; Routh, Johnston, Harris, & Chitwood, ). In addition, these neurons display a depolarizing sag in response to hyperpolarizing current pulses, indicative of the hyperpolarization‐activated cation current I h (Gasparini & DiFrancesco, ; Gasselin, Inglebert, & Debanne, ; van Welie, van Hooft, & Wadman, ) (Figure c, n = 112).…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal CA1 pyramidal neurons filled with Alexa Fluor 488 dye (Thermo Fisher Scientific, Rockford, IL, USA) via patch electrode have a distinctive dendritic morphology (Figure a,b). Voltage response to current steps (I‐V curve) with duration of 600 ms ranging from −100 to +200 pA with 20 pA increments, exhibited the characteristic pattern of action potential firing of hippocampal CA1 neurons, with peak depolarization ~50 mV (Martina, Schultz, Ehmke, Monyer, & Jonas, ; McKiernan & Marrone, ; Routh, Johnston, Harris, & Chitwood, ). In addition, these neurons display a depolarizing sag in response to hyperpolarizing current pulses, indicative of the hyperpolarization‐activated cation current I h (Gasparini & DiFrancesco, ; Gasselin, Inglebert, & Debanne, ; van Welie, van Hooft, & Wadman, ) (Figure c, n = 112).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, prior studies have identified deficits in spatial memory (9,11), working and episodic memory (8,10) and recognition memory (12), when comparing young, adult mice with older sex-matched animals. The hippocampus is the brain region associated with learning and memory formation and is particularly vulnerable to age-related changes in humans and rodents (13)(14)(15)(16). Deficits in a number of cellular processes have been suggested as underlying causes based on correlative evidence, including protein synthesis (17), metabolism (18), inflammation (19), and immune responses (9,11,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, prior studies have identified deficits in spatial memory ( Villeda et al, 2011 ; Villeda et al, 2014 ), working and episodic memory ( Yousef et al, 2019 ; Castellano et al, 2017 ) and recognition memory ( Cabral-Miranda et al, 2020 ), when comparing young, adult mice with older sex-matched animals. The hippocampus is the brain region associated with learning and memory formation and is particularly vulnerable to age-related changes in humans and rodents ( Disterhoft and Oh, 2007 ; McKiernan and Marrone, 2017 ; Oh et al, 2010 ; Rizzo et al, 2014 ). Deficits in a number of cellular processes have been suggested as underlying causes based on correlative evidence, including protein synthesis ( Schimanski and Barnes, 2010 ), metabolism ( Azzu and Valencak, 2017 ), inflammation ( Franceschi et al, 2000 ), and immune responses ( Villeda et al, 2011 ; Villeda et al, 2014 ; Baruch et al, 2014 ; Dulken et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal CA1 pyramidal neurons exhibit various multi-timescale firing patterns (from simple spiking to bursting) and play an essential role in shaping spatial and episodic memory [31]. In the last two decades, several biophysiological models of the CA1 pyramidal (CA1Py) neurons ranging from single compartmental biophysiological and phenomenological models [32][33][34] to detailed morphology-based multi-compartmental models [35][36][37][38][39][40][41] have been developed to understand the contributions of various ion-channels in diverse firing patterns (e.g., simple spiking to bursting) exhibited by the CA1Py neurons.…”
Section: Synthetic Datamentioning
confidence: 99%